2015
DOI: 10.1021/es5061963
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Nonlinear Adsorption to Carbon with a Single Chemical Parameter: A Lognormal Langmuir Isotherm

Abstract: Predictive models for linear sorption of solutes onto various media, e.g., soil organic carbon, are well-established; however, methods for predicting parameters for nonlinear isotherm models, e.g., Freundlich and Langmuir models, are not. Predicting nonlinear partition coefficients is complicated by the number of model parameters to fit n isotherms (e.g., Freundlich (2n) or Polanyi-Manes (3n)). The purpose of this paper is to present a nonlinear adsorption model with only one chemically specific parameter. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The Freunlich equation assumes that adsorption is via a multimolecular layer and a saturation adsorption quantity cannot be acquired due to increasing adsorbance all the time. 55,56 The fitting results suggested that adsorption action was via a monomolecular layer and the adsorption process was related to chemical adsorption, which was consistent with previous conclusions.…”
Section: Adsorption Isotherm and Thermodynamic Analysissupporting
confidence: 90%
“…The Freunlich equation assumes that adsorption is via a multimolecular layer and a saturation adsorption quantity cannot be acquired due to increasing adsorbance all the time. 55,56 The fitting results suggested that adsorption action was via a monomolecular layer and the adsorption process was related to chemical adsorption, which was consistent with previous conclusions.…”
Section: Adsorption Isotherm and Thermodynamic Analysissupporting
confidence: 90%
“…Although data suggest that partitioning of PAH is better described with a 2‐C model, applying this type of modeling framework in a risk assessment may require significant effort to reliably characterize site‐specific partitioning coefficients for K BC and K OC for multiple PAHs. Recent efforts have demonstrated that advances in partitioning modeling may be a feasible option (Davis and Di Toro , ). However, direct porewater measurement may be a more practical solution for refined risk evaluations.…”
Section: Resultsmentioning
confidence: 99%
“…and Eq. , respectively . CeQe=1KnormalLQnormalm+CeQmlogQnormale=logCnormalen+logKnormalFwhere C e (μg/mL) and Q e (mg/g) are the equilibrium concentration and the equilibrium adsorption capacity of E1, respectively, Q max (mg/g) is the maximum adsorption capacity, and K L (L/mg) is the Langmuir constant, K F and n are the Freundlich constants.…”
Section: Resultsmentioning
confidence: 99%